Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.18502/npt.v7i3.3347
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of communication skills and emotional expressions among nursing students in Turkey: A public university sample

Abstract: Background & Aim: Expressing emotions is very important both in interpersonal relationships and in the protection and maintenance of the individual's mental health. However, the individual must have certain skills to express his feelings healthily. The most important of these is communication skills. This research aimed to examine the correlation between communication skills and emotional expressions of nursing students. Methods & Materials: This correlational study was conducted among nursing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Through their intensive training, students in these fields develop strategies related to the regulation of emotions. The average found in our research is lower than that detected in a recent study among nursing students in a Turkish public university, where the total BEQ score was found to be on average 79.45 ± 10.11 [16]. This is in part related to the fact that participants in our study majoring in paramedical sciences include not only nurses but also physiotherapists, laboratory and biomedical imaging technicians as well as nutritionists.…”
Section: Discussioncontrasting
confidence: 91%
“…Through their intensive training, students in these fields develop strategies related to the regulation of emotions. The average found in our research is lower than that detected in a recent study among nursing students in a Turkish public university, where the total BEQ score was found to be on average 79.45 ± 10.11 [16]. This is in part related to the fact that participants in our study majoring in paramedical sciences include not only nurses but also physiotherapists, laboratory and biomedical imaging technicians as well as nutritionists.…”
Section: Discussioncontrasting
confidence: 91%
“…In the limited number of studies conducted to determine the communication skills of nursing students in Turkey, it was found that T A B L E 1 Mean score of the students on the Resilience Scale the communication skills of the nursing students were better than the average or even strong. 20,21 Nursing is a profession based on human relations and learning communication skills primarily occurs during the educational process. Training nurses with well-developed communication, personal development, critical thinking, and problem-solving skills is one of the primary goals of nursing education in Turkey; theoretical lessons and workshops are designed to achieve these goals.…”
Section: Discussionmentioning
confidence: 99%
“…When the students' mean scores for the whole CSS and its subdimension were evaluated, it was determined that the participants' communication skills were strong. In the limited number of studies conducted to determine the communication skills of nursing students in Turkey, it was found that the communication skills of the nursing students were better than the average or even strong 20,21 . Nursing is a profession based on human relations and learning communication skills primarily occurs during the educational process.…”
Section: Discussionmentioning
confidence: 99%
“…Communication skills can also be summarized as sensitivity to verbal and nonverbal messages, active listening, and effective reactions (Gibson & Mitchell, 2008). A number of studies have been conducted recently on communication skills, which is a very important subject (Claramita et al, 2020;Fallahi et al, 2020;Bijen, 2020;Cho et a l., 2020;Kaplan Serin et al, 2020;Küçükkaragöz & Karakoyun, 2020;Mendi et al, 2020;Nurani et al, 2020;Uygun & Arıbaş, 2020;Yavuz & Güzel, 2020;Yıldırım et al, 2020).…”
Section: Introductionmentioning
confidence: 99%